2021
DOI: 10.5558/tfc2021-006
|View full text |Cite
|
Sign up to set email alerts
|

Climate, radial growth, and mortality associated with conifer regeneration infected by root disease (Armillaria ostoyae)

Abstract: Tree root disease caused by the pathogen Armillaria ostoyae (Romagn.) Herink has notable influence on bio-economic systems of southern British Columbia (BC) and the northwestern United States. Annual radial growth and mortality trends of regeneration associated with A. ostoyae during the first 21 years of a plantation were investigated. Our dendrochronological approach focused on a plantation established in 1991 with Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco), western larch (Larix occidentalis Nutt.), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Of special note, P. menziesii with higher levels of drought tolerance were also associated with higher levels of resistance to Armillaria root disease, caused by A. solidipes (Cruickshank and Filipescu, 2017). Furthermore, summer droughts were associated with increased A. solidipes-caused mortality of P. menziesii in southern BC, Canada (Murray and Leslie, 2021). These findings further support that climatic maladaptation of P. menziesii will lead to increased infection by A. solidipes.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Of special note, P. menziesii with higher levels of drought tolerance were also associated with higher levels of resistance to Armillaria root disease, caused by A. solidipes (Cruickshank and Filipescu, 2017). Furthermore, summer droughts were associated with increased A. solidipes-caused mortality of P. menziesii in southern BC, Canada (Murray and Leslie, 2021). These findings further support that climatic maladaptation of P. menziesii will lead to increased infection by A. solidipes.…”
Section: Discussionmentioning
confidence: 52%
“…Changing climate, extreme weather events (e.g., drought, high temperatures), and/or other disturbances (e.g., fire, insect attack, and forest management activities) are causing increased disease severity by A. solidipes on stressed P. menziesii (Morrison, 2011;Murray and Leslie, 2021). Armillaria root disease, in conjunction with the adverse impacts from climate and extreme weather events, can predispose trees to attack by other biotic agents including bark beetles (e.g., Hertert et al, 1975;Kulhavy et al, 1984;Tkacz and Schmitz, 1986), which can result in tree mortality and increased availability of nutritional substrates for inoculum of Armillaria species that can, in turn, contribute to future disease on the site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors contribute to inoculum quantity and quality, which needs to be assessed to account for changes in disease behavior. However, Murray and Leslie (2021) showed that levels of Armillaria root disease intensity are associated with drought events where the disease is present in a plantation in southern British Columbia (i.e., Type 2 climate–disease). Some root diseases such as laminated root rot caused by Coniferiporia weirii (formerly Phellinus weirii ) are not associated with host stress and any climate effects on disease behavior may be related to vegetative growth and sporulation similar to stem decay fungi (i.e., Type 1 climate–disease).…”
Section: Discussionmentioning
confidence: 99%
“…Known at the genus-level as Armillaria root-rot disease [3][4][5] , the most common pathogenic species is A. mellea sensu lato, which has been reported to infect >500 plant species 1,6,7 and is solely responsible for up to 40% annual loss of vinegrape in California 8 . A. ostoyae is responsible for significant losses in conifer forests 9,10 .…”
Section: Introductionmentioning
confidence: 99%